Checklist of Cerambycidae (Coleoptera) primary types of the Museu Nacional, Rio de Janeiro, Brazil, with a brief history of the collection - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2016)
A checklist of the Cerambycidae (Coleoptera) primary types deposited in the Museu Nacional, Universidade Federal do Rio de Janeiro, Rio de Janeiro, Brazil is given. There are 1,044 primary types. Lectotype designation for Megacyllene castroi (Prosen, 1947) is proposed. A brief history of the collection of Cerambycidae of the Museu Nacional is presented.